Association between opioid agonist therapy use and HIV testing uptake among people who have recently injected drugs: a systematic review and meta‐analysis. (3rd February 2021) - Ferraro, Claire F.; Stewart, Daniel E.; Grebely, Jason; Tran, Lucy T.; Zhou, Shally; Puca, Carla; Hajarizadeh, Behzad; Larney, Sarah; Santo, Thomas; Higgins, Julian P. T.; Vickerman, Peter; Degenhardt, Louisa; et al.
Abstract: Background and aim: Globally, nearly one in five people who inject drugs (PWID) are living with HIV, and the rate of new HIV infections in PWID is increasing in some settings. Early diagnosis is crucial for effective HIV control. We reviewed the evidence on the association between opioid agonist therapy (OAT) and HIV testing uptake among PWID. Methods: We conducted a systematic review searching MEDLINE, Scopus, Web of Science, Cochrane Central Register of Controlled Trials and PsycINFO for studies published from January 2000 to March 2019. Reference lists and conference proceedings were hand‐searched. Observational and intervention studies were eligible for inclusion. Risk of bias was assessed using the Risk of Bias in Non‐Randomised Studies of Interventions (ROBINS‐I) tool. Meta‐analyses were conducted using random‐effects models. Results: Of 13 373 records identified, 11 studies from Australia, Europe, Malaysia and the United States were included. All studies had at least a serious risk of bias, largely due to confounding and selection bias, making it difficult to draw causal conclusions from the evidence. Ten studies provided data on the association between current OAT use and recent HIV testing. Six showed a positive association, while four provided little evidence of an association: pooled odds ratio (OR) = 1.71, 95% confidence interval (CI) = 1.28–2.27. Looking at having ever been on OAT and having ever been HIV tested, seven studies showed a positive association and three showed either weak or no evidence of an association: pooled OR = 3.82, 95% CI = 2.96–4.95. Conclusions: Opioid agonist therapy may increase uptake of HIV testing among people who inject drugs, providing further evidence that opioid agonist therapy improves the HIV treatment care cascade.